Integrated tecnologikal operations effects on the structure and properties of heat-resistant nickel alloy HA3DK-VI - Жеманюк, П. Д.; Клочихин, В. В.; Лысенко, Н. А.; Наумик, В. В. (Eastern-European Journal of Enterprise Technologies, 2013)
It is studied the complex influence of technological operations of fusion thermal-time treatment (TTT), retrofitting by ultra disperse particles (UDP) of carbonitride of titan Ti(C,N) and subsequent hot isostatical pressing (HIP) on a structure and properties of the heatproof nickel alloy ЖС3ДК-ВИ, after standard heat treatment. Conducting of fusion thermal-time treatment (TTT) contributes to a certain enlargement macrograin and modification with carbonitride particles Ti(C,N) – leads to a refinement of the grain. The most favorable combination of strength and plastic characteristics, as well as long-term strength at 850 °C and a load of 35 kgf/mm2 characterized by stability test results obtained on the modified with Ti(C,N) samples. The operation HIP promotes "healing" shrinkage defects such as pores and microporosity.